2012
DOI: 10.1089/jcr.2012.0024
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Energy Drink on Physical and Cognitive Performance in Trained Cyclists

Abstract: Dedication This work is dedicated to those who have supported me outside of my graduate studies over the last few years. My family deserves as much credit as anyone for the work generated as part of this study. Namely, Kristin Bagby, Christine Lassiter, Mechelle Lassiter, Bette Rose Ryan, and Michele Poague deserve recognition; without them I would not have been able to work as tirelessly as I have on this project. v Acknowledgements Many individuals contributed significantly to the completion of this project.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 110 publications
(265 reference statements)
0
11
0
Order By: Relevance
“…Caffeine is the primary ingredient found within energy drinks that may alter performance and cardiovascular measures. Caffeine is a psychoactive drug known to allay fatigue and improve endurance performance and is one of the most widely used drugs in the world (6,8,10,15,21,22,25,27,34). In previous research caffeine has been shown to improve performance (8,10,15,21,22,25,34).…”
Section: Introductionmentioning
confidence: 99%
“…Caffeine is the primary ingredient found within energy drinks that may alter performance and cardiovascular measures. Caffeine is a psychoactive drug known to allay fatigue and improve endurance performance and is one of the most widely used drugs in the world (6,8,10,15,21,22,25,27,34). In previous research caffeine has been shown to improve performance (8,10,15,21,22,25,34).…”
Section: Introductionmentioning
confidence: 99%
“…The use of energy drinks and energy shots is high among US military personnel and has been a subject of ongoing controversy for several years . Proponents claim that energy drinks improve athletic performance . Given that the primary active ingredient in most energy products is caffeine, this is expected, since caffeine is a known ergogenic aid for endurance and anaerobic activities .…”
Section: Introductionmentioning
confidence: 99%
“…Ingestion of as low as 3 mg/kg body weight 1 h before exercise has been found to be effective at increasing exercise time to exhaustion at exercise intensities of 70-80 % maximal oxygen consumption (VO 2 max) [17,28]. However, energy drinks containing much lower amounts of caffeine have also been found to have effective ergogenic properties [16,21]. The reasons behind the ergogenic effects of caffeine, however, are not clear, but have been associated…”
Section: Introduction ▼mentioning
confidence: 99%
“…However, there is the possibility that providing the caffeine with a NO source improved the efficacy of the caffeine. Previous research with energy drinks containing relatively low levels of caffeine have been found to improve cycling time trial performance without an increase in perceived effort [16,21]. Improvements in aerobic performance by increasing blood nitrate levels either by consumption of sodium nitrate or beetroot juice has been associated with an increase in oxygen efficiency [2,3,19,20].…”
mentioning
confidence: 98%